KEBIJAKAN MARITIM INDONESIA DALAM MENUNJANG SISTEM KEAMANAN TRANSPORTASI LAUT - Naufal Muammar; Ansyari Mosyofa (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2024)
Indonesian Maritime Policy in Supporting the Maritime Transportation Security System has become a main focus in recent years. Strong support from the government, strict maritime regulations, regional cooperation, and investment in maritime infrastructure have played a key role in maintaining the security and smoothness of maritime transportation in this island nation. Maritime infrastructure, such as modern ports, shipping networks, and supporting facilities, not only drives the economy by facilitating trade and connectivity between islands but also supports a growing tourism sector. Efforts to implement maritime policy involve strict regulations, cooperation between countries, developing maritime security capabilities, promoting environmentally friendly maritime transportation, as well as increasing ship and port security. All of this aims to maintain global trade stability, improve the economy, and ensure the safety of maritime transportation in Indonesian waters. With the adoption of the Indonesian Maritime Doctrine in 2015 and the Republic of Indonesia Law No. 17 of 2008 concerning Shipping, Indonesia increasingly emphasizes its commitment to maintaining the security and safety of maritime transportation as an integral part of the national outlook and security of the Republic of Indonesia as a maritime country.